DESIGN OF LOWPASS FILTER WITH LOW TOTAL HARMONIC DISTORTION - MOHAMED MASARIK, MUHAMMAD SAFWAN (Universiti Teknologi PETRONAS, 2017)
This research is conducted to design a lowpass filter with low total harmonic distortion (THD). The research focuses on the suitable design synthesis of lowpass filter with cutoff frequency at 500kHz, -35 dB attenuation at 1000kHz and -100 dB response of total harmonic distortion. Elliptic filter topology is selected after comparing with Maximally flat, Chebyshev and Inverse Chebyshev topologies because Elliptic filter gives steepest attenuation and lowest THD reading. Elliptic filter results in lowest THD at -35.65 dB. Additionally, research was done on the effect of inductor’s number and types on the harmonic responses of filters. Comparison of inductors and capacitors were made and the best component with expected lowest THD was selected for fabrication. Therefore Ferrite pot core inductor and Polystrene film capacitor was selected. Stated design hypothesis is the design of lowpass filter with low THD is possible with less inductor section.